Green Synthesis Of Gold Nanoparticles Using Tagetes Erecta L. (Mari Gold) Flower Extract & Evaluation Of Their Antimicrobial Activities - KRISHNAMURTHY NB; NAGARAJ B; BARASA MALAKAR; LINY P; DINESH R (International Journal of Pharma and Bio Sciences, 2012)
An environment friendly technique for green synthesis of gold nanoparticles has been developed using the flower extract of Tagetes Erecta as reducing agent for reduction of Au3+ in aqueous solution. The nanoparticles obtained were characterized by UV-visible spectroscopy. The UV- visible spectra indicate a strong Plasmon resonance that is located at 500 nm. The morphology and size of the biologically synthesized gold nanoparticles were determined using TEM. The images clearly show that the average size of the nanotriangles is about 200 nm, while, the spherical like particles show very small size about 8-10 nm. The antimicrobial activities of obtained gold particles have been studied with antibiotic, which show more inhibitory zones than the standard antibiotics.